Perbandingan Efektivitas Bioadsorben Serbuk Kulit Singkong Dan Serbuk Kulit Pinang Terhadap Logam Pb (II) Limbah Cair Laboratorium Farmasi - Morijan, Risky asrina; Leswana, Nurillahi Febria; Butar-Butar, Maria Elvina Tresia (Jurusan Farmasi Poltekkes kemenkes Makassar, 2024)
Comparison of bio-adsorbent effectiveness of cassava shell powder and betel nut powder against Pb (II) metal of pharmaceutical laboratory liquid waste Pharmaceutical laboratory liquid waste is a source of heavy metal pollutants that can be harmful to living things if not treated properly. One of these heavy metals is lead (Pb), which if discharged directly into the environment can damage the environment and cause health problems. To adsorb these heavy metals, bio-adsorbents can be used, including cassava peel and areca nut peel because they contain cellulose and pectin. In this study, measurements of Pb levels in the waste before and after adsorption were carried out using the UV-visible spectrophotometry method, and the reagent used was alizarin sulfonate from variations in pH. optimum, optimum contact time and optimum mass of the validation method carried out is precision and accuracy. The aim of this study was to determine the comparison of the adsorption effectiveness of cassava peel powder and areca nutshell powder bioadsorbents against Pb metal in pharmaceutical laboratory wastewater. The results obtained were the optimum areca nut skin at pH 5, contact time 45 minutes, and mass 175 mg. Whereas cassava peel at pH 5, contact time 75 minutes, and mass 75 mg. The adsorption effectiveness of areca nut peels is better than that of cassava peels with an adsorption percentage of areca nut peels of 83.38%, while cassava peels are 54.46%. The results of the method validation are declared valid by showing an accuracy value in the range of 80-110% and a precision value of not more than 2%. Limbah cair laboratorium farmasi merupakan sumber pencemar logam berat yang dapat berbahaya bagi makhluk hidup jika tidak diolah dengan baik. Salah satu logam berat tersebut adalah timbal (Pb) yang jika dibuang langsung ke lingkungan dapat merusak lingkungan dan gangguan kesehatan. Untuk mengadsorpsi logam berat tersebut dapat digunakan bioadsorben salah satunya adalah kulit singkong dan kulit pinang karena mengandung selulosa dan pektin, pada penelitian ini dilakukan pengukuran kadar Pb dalam limbah sebelum dan sesudah adsorbsi menggunakan metode spektrofotometri UV-Visible dan reagen yang digunakan alizarin sulfonat dari variasi pH optimum, waktu kontak optimum, dan massa optimum metode validasi yang dilakukan adalah presisi dan akurasi tujuan penelitian ini dilakukan adalah untuk menentukan perbandingan efektivitas adsorbsi bioadsorben serbuk kulit singkong dan serbuk kulit pinang terhadap logam Pb limbah cair laboratorium farmasi. Hasil yang diperoleh adalah kulit buah pinang optimum pada pH 5, waktu kontak 45 menit, dan massa 175 mg. Sedangkan pada kulit singkong pada pH 5, waktu kontak 75 menit, dan massa 75 mg. Efektivitas adsorbsi kulit pinang lebih baik dibandingkan dengan kulit singkong dengan persentase adsorbsi kulit pinang sebesar 83,38%, sementara kulit singkong 54,46%. Hasil validasi metode dinyatakan valid dengan menunjukkan nilai akurasi pada rentang 80-110% dan nilai presisi tidak lebih dari 2%.